Electrically Tunable and Reconfigurable Topological Edge State Laser - Hang Li; Ruizhe Yao; Bowen Zheng; Sensong An; Mohammad Haerinia; Jun Ding; Chi-Sen Lee; Hualiang Zhang; Wei Guo (Optics, 2022)
Incorporating active components in photonic structures with a topological configuration has been shown to achieve lasing at topological edge states. Here, we report an electrically tunable topological edge-state laser in a one-dimensional complex Su–Schrieffer–Heeger chain. The proposed design is realized in an electrically injected Fabry–Perot (FP) laser chain. The lasing in topologically induced edge states is experimentally observed and a selective enhancement is realized by introducing a topological defect in the center. This work presents a versatile platform to investigate novel concepts such as the topological mode for mainstream photonic applications.